Clinician Wellness During the COVID-19 Pandemic: Extraordinary Times and Unusual Challenges for the Allergist/Immunologist - Bansal, Priya (J Allergy Clin Immunol Pract, 2020)
The global spread of coronavirus disease 2019 (COVID-19) has caused sudden and dramatic societal changes. The allergy/immunology community has quickly responded by mobilizing practice adjustments and embracing new paradigms of care to protect patients and staff from severe acute respiratory syndrome coronavirus 2 exposure. Social distancing is key to slowing contagion but adds to complexity of care and increases isolation and anxiety. Uncertainty exists across a new COVID-19 reality, and clinician well-being may be an underappreciated priority. Wellness incorporates mental, physical, and spiritual health to protect against burnout, which impairs both coping and caregiving abilities. Understanding the stressors that COVID-19 is placing on clinicians can assist in recognizing what is needed to return to a point of wellness. Clinicians can leverage easily accessible tools, including the Strength-Focused and Meaning-Oriented Approach to Resilience and Transformation approach, wellness apps, mindfulness, and gratitude. Realizing early warning signs of anxiety, depression, substance abuse, and posttraumatic stress disorder is important to access safe and confidential resources. Implementing wellness strategies can improve flexibility, resilience, and outlook. Historical parallels demonstrate that perseverance is as inevitable as pandemics and that we need not navigate this unprecedented time alone.